Peran Koperasi Dalam Pemberdayaan Ekonomi Masyarakat: Analisis KSPPS BMT Berkah Madani - Siregar, Gita Ba’in; Abidin, Amelia Zayyana; Damayanti, Nimas; Ulhaq, Naufal Dhiya; Pratama, FX Asa Putra; S, Saridawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The objectives of this study are to analyze the role of KSPPS BMT Berkah Madani in community economic empowerment. Cooperatives play an important role in business, especially in particular, they contribute to improve the economic well being of the community. As a business entity run by its members, cooperatives not only aim for business, but also to improve the social and economic lives of its members. This research uses a qualitative method that involves interviews with sources, object observation by directly observing the research location. This study's findings indicate that the role of KSPPS BMT Berkah Madani can encourage the economy of the community, especially cooperative members through products such as financing and savings. The existence of KSPPS BMT Berkah Madani also helps develop employment opportunities and improve the quality of members' businesses.